On the importance of placebo and nocebo effects in international trade - Lucian Cernat (European Centre for International Political Economy (ECIPE), 2024)
Trade agreements are powerful drivers of global economic integration, leading to increased trade flows between countries. Usually, trade agreements are extensive documents with hundreds of provisions and different levels of enforceability. Are all these provisions useful, even those that are "best endeavours" and do not introduce legally binding obligations on trading partners? This policy brief proposes a new methodological approach to evaluate these effects. The basic idea is inspired by the "placebo effect" in medicine: under the right conditions, one can get positive results, even when the actual interventionis simply a "sugarpill".Similarly,trade policies may have positive effects even when they lack strong, enforceable commitments. A placebo trade policy effect can emerge from "soft provisions" that bring positive trade effects, compared to the "do nothing" scenario. The main hypothesis behind this new methodology is that even if trade interventions lack the force to solve problems outright, a positive placebo effect can arise if stakeholders believe that such a policy will generate favourable market access. Conversely, a negative nocebo effect might emerge when stakeholders are convinced that certain trade policy initiatives (notably FTAs) have a detrimental impact, despite undeniable evidence to the contrary. The paper concludes with a few concrete examples illustrating both the placebo and nocebo effects and identifies factors that may lead to more positive outcomes from current and future trade policies.
Keywords: 330